Geography of Boredom. On Bogomil Raynov’s Travelling in Everyday Life - Stoyanova, Nadezhda (Labyrinth, 2022)
Thе aim of the paper is to present the problem of boredom in Bogomil Raynov’s fourth book Travelling in Everyday Life (1945). The interpretation of boredom in the novel is seen as based on the idea of a mismatch between expectation and experience. The expectation of the individual turns out to be modeled by the mass commercialization of the 20th century. The "cultural industry" replaces the sublime ideas of the romantic poetics with superfluous clichés, which deny the world its unpredictability, its unexpectedness. It is these kinds of clichés that are subject of irony in Bogomil Raynov's novel – false expectations create a false feeling of boredom. Boredom as a problem has been rarely discussed either by Bulgarian authors, or by Bulgarian literary historians, therefore this paper tries not only to focus scholars’ attention on it, but also to interprete it.